Resisting the Effects of Neoliberalism on Public Policy; Comment on "Implementing Universal and Targeted Policies for Health Equity: Lessons From Australia" - Dennis Raphael; Toba Bryant (Kerman University of Medical Sciences, 2022)
Fisher and colleagues carefully review the extent to which health equity goals of availability, affordability, and acceptability have been achieved in the areas of national broadband network policy and land-use policy, in addition to the more traditional areas of primary healthcare and Indigenous health in Australia. They consider the effectiveness of policies identified as either universal, proportionate-universal, targeted or residualist in these areas. In this commentary we suggest future areas of inquiry that can help inform the findings of their excellent study. These include the impacts of Australia being a liberal welfare state and how acceptance of neoliberal approaches to governance makes the achieving of health equity in these four policy areas difficult.